Sex differences in long-term kidney fibrosis following neonatal nephron loss during ongoing nephrogenesis - Carlos Menendez-Castro; Nada Cordasic; Fabian B. Fahlbusch; Joachim Woelfle; Karl F. Hilgers; Andrea Hartner (SpringerOpen, 2023)
Abstract Background Clinical studies suggest that female sex plays a protective role in the development and progression of kidney disease. Recent experimental studies indicate that in male rats early nephron loss under ongoing nephrogenesis is accompanied by severe long-term sequelae. In humans, nephron formation occurs mainly in the third trimester, ceasing with 36 weeks of gestation. Due to perinatal complications, preterm infants delivered during this vulnerable period may undergo acute nephron loss. In rats nephrogenesis persists until postnatal day 10, reflecting the situation of human preterms with persisting nephrogenesis. In our animal model of neonatal uninephrectomy, female and male rats were uninephrectomized at day 1 of life. Hypothesizing sex-dependent differences, long-term renal outcome was assessed after 1 year. Results In both sexes, neonatal uninephrectomy was not followed by arterial hypertension at 1 year of age. Compensatory weight gain and glomerular hypertrophy of the remaining kidney occurred in uninephrectomized female and male animals. Selected markers of interstitial inflammation and fibrosis were regulated sex-dependently. The expression of monocyte chemoattractant protein-1 was increased in females, while tubulointerstitial infiltration by M1 macrophages was significantly higher in males after neonatal uninephrectomy. Neonatally uninephrectomized male rats had more glomerulosclerosis and podocyte damage compared to females, which was assessed by a semiquantitative score and desmin staining. RT-PCR revealed that after neonatal uninephrectomy in the remaining contralateral kidney of female rats the expression of candidate genes of renal development and function, i.e., wt-1, nephrin, synaptopodin, gdnf, and itga8 was higher than in males. Conclusions Based on these observations we conclude that female sex is protective in the long-term response of the kidney to acute nephron loss under active nephrogenesis.